Police Efforts in Combating Trafficking in Persons with the Exploitation Mode of the Area and Disabled People to Become Beggars - Febriana Citra (IHSA Institute, 2019)
Crime of trafficking in persons is carried out using various modes, one of which is to exploit the elderly and disabled people to become beggars. The police follow up on the crime to carry out criminal acts in accordance with the duties, functions and authority of the police as law enforcement officers. The problems of this study are: (1) What is the police's effort in dealing with the crime of trafficking in persons with the exploitation mode of the elderly and disabled people to become beggars? (2) What are the inhibiting factors in the police's efforts in dealing with the crime of trafficking in persons with the exploitation of the elderly and disabled people to become beggars? The problem approach in this study uses a normative and empirical juridical approach. The research data consisted of primary data and secondary data. Research resource persons included Lampung Regional Police Investigators, Bandar Lampung City Social Service Officers and Unila Law Faculty Criminal Law Lecturers. Data collection is done by literature study and field studies. Data is analyzed qualitatively. The results of the study and discussion show: (1) Police efforts in the handling of criminal acts of trafficking in persons with exploitation of the elderly and disabled people to be used as beggars by the Lampung Regional Police through pre-emptive, preventive and repressive efforts. Pre- emtive efforts are carried out with socialization activities in collaboration with the Social Service and relevant government institutions. Preventive efforts are carried out by patrolling and monitoring the activities of the elderly and people with disabilities. Repressive efforts are carried out by investigation and investigation. (2) The inhibiting factors of police efforts in dealing with criminal acts of trafficking in persons with the exploitation mode of the elderly and disabled people to become beggars are factors of law enforcers, namely quantitatively the number of investigators is still limited and the quality of human resources is still not optimal tactics and investigation technique. The community factor is that the community does not report if they are aware of the crime of trafficking in persons with exploitation mode of the elderly and disabled people to be used as beggars. Cultural factors, namely people assume that begging is not a crime or acrime.